Analisis perbandingan bahan dan jumlah perekat terhadap briket tempurung kelapa dan ampas tebu - Welly Deglas; Fransiska Fransiska (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
The aim of this research was to study the effect of comparative analysis of ingredients and the amount of adhesive on the coconut shell charcoal briquettes and bagasse charcoal. This research used Split Plot Design that consisted of two factors. The first factor is the total ratio of coconut shell charcoal and bagasse charcoal and coconut shell charcoal and bagasse charcoal 1: 1 (L1), 1: 2 (L2) and 1: 3 (L3), while the second factor was the amount of sago adhesive as plots section, consisting of: 10% (P1), 20% (P2) and 30% (P3). The parameters analyzed include: heating value, moisture content, ash and volatile matter. The results showed that the amount of adhesive greatly affected the briquette charcoal produced, the addition of the amount of adhesive would reduce the briquette's heating value, as well as the water content, ash content and evaporation rate increased with the addition of the amount of adhesive. Comparison of coconut shell charcoal and bagasse charcoal can influence to cause higher levels of volatile matter because the level of sugarcane charcoal volatile matter is higher than coconut shell charcoal which has lower volatile matter levels. Judging from the heating value in this study, the best results in this study were in the treatment of P1L1, namely the ratio of coconut shell charcoal and bagasse 1:1 with the amount of sago adhesive 10% with a heating value 5687.45%.